Appendicular Skeletal Muscle Index Is Positively Related to Mediterranean Diet Adherence in University Students - Paraskevi Detopoulou; Olga Magni; Ioanna Pylarinou; Despoina Levidi; Vassilios Dedes; Milia Tzoutzou; Konstantina Argyri; Evangelia Fappa; Aristea Gioxari; George Panoutsopoulos (Diseases)
Skeletal muscle is associated with cardiometabolic health. The appendicular skeletal muscle index (aSMI) represents the skeletal muscle mass “corrected” for height and constitutes a clinically applicable feature of sarcopenia. The relation of the aSMI with dietary habits is not clear, especially in young adults. The present pilot study aimed to investigate the relationship between the aSMI and Mediterranean diet adherence in young adults. A cross-sectional study of 151 university students was conducted. Anthropometry and bioimpedance analysis (TANITA-MC780) were performed. The aSMI was calculated as the sum of the upper and lower extremity muscle masses divided by height squared. The HPAQ questionnaire was used for physical activity evaluation. A validated food frequency questionnaire was used for dietary assessment, and the Mediterranean Diet Score (MedDietScore) was calculated. Multivariate linear regression models with log-aSMI as a dependent variable were applied. The MedDietScore was positively related to log-aSMI in the total sample (B = 0.009, SE = 0.004, p = 0.05, R2 for total model = 71%) irrespective of gender, age, ΒΜΙ, smoking, physical activity, and academic year and in males (B = 0.027, SE = 0.011, p = 0.023 R2 for total model = 37%) irrespective οf age and ΒΜΙ. The positive association of the MedDietScore with aSMI supports the importance of the adoption of a Mediterranean dietary pattern—rich in plant proteins and antioxidant/anti-inflammatory compounds—in maintaining/attaining muscle mass in young subjects.